STRATEGI PENGEMBANGAN USAHA STRAWBERRY DI AGROWISATA PETIK STRAWBERRY - Ana Arifatus Sa’diyah; Anung Preseio Nugroho; Adrianus Bria (Hasanuddin University, 2020)
The application of appropriate strategies can encourage tourism development that emphasizes the tourism principle that tourism must depart from the awareness of the values ​​of community needs as an effort to build tourism that is more beneficial to the needs, initiatives and opportunities of local communities. This study aims to: analyze the strawberry picking agro-tourism development strategy in Pandanrejo Village, Bumiaji District, Batu City, analyze the factors that support the development of picking strawberry agro-tourism in Pandanrejo Village, Bumiaji District, Batu City, analyze the factors that hinder the development of picking agro-tourism strawberry in Pandanrejo Village, Bumiaji District, Batu City. The research location in strawberry picking agro-tourism in Pandanrejo Village, Bumiaji District, Batu City, East Java. Data obtained by the method of observation, interviews and documentation. The validity of the data was tested by using triangulation technique. This study uses a SWOT analysis. The results of the analysis show that strategies that can be carried out for the development of strawberry picking agro-tourism are optimizing facilities and improving servants and promotion of picking strawberry attractions, conducting product reservation by maximizing existing land, compiling tour packages with various price levels, working with travel agents and improving resource quality. human.